Identification and analysis of the decisive factors of local development for the use of natural gas in the ceramist industries of Mato Grosso do Sul (Brazil) - Guerra, Sinclair Mallet Guy; Pereira Pinto, João Onofre; Merighi, Cristiane de Castilho (Interações, 2016)
The present article is part of research in development, together with the USP/IEE, UFMS and UCDBuniversities, the aim of which is to identify and to analyze qualitatively and quantitatively the decisive factors for theuse of natural gas from local development in the ceramist industries of Mato Grosso do Sul. Natural gas is not usedyet as an alternative source of energy on a large scale in the State. It can be considered as one of the results of thevalorization of socioeconomic policies, of the local culture and of the environment, preserved as part of the localidentity of the human being in his improvement of life quality.